Judicial Reasoning on Unlawfulness in Onslag Decisions in Corruption Cases - Subihat, Ihat (JURNAL USM LAW REVIEW, 2026)
This study analyzes judicial law finding (rechtvinding) in High Court Decision Number 25/PID.SUS/2021/PT/BDG, focusing on the interpretation of the element of unlawfulness in an onslag van alle rechtsvervolging ruling within corruption cases involving budget switching policies in the education sector. The research addresses the tension between legal certainty and substantive justice, particularly the tendency to criminalize administrative discretion without adequate assessment of material unlawfulness and mens rea. This study employs a normative legal method with statutory and case approaches, supported by qualitative interpretative and argumentative analysis of legal materials. The findings demonstrate that the panel of judges applied a contextual and substantive approach by integrating formal and material unlawfulness, emphasizing intent, consequences, and proportionality. Although procedural irregularities were identified, the absence of malicious intent and state financial loss justified the application of onslag as a manifestation of the principles of ultimum remedium, proportionality, and subsidiarity. The novelty of this research lies in the formulation of the Theory of Decriminalization of Functional Discretion, which offers a conceptual framework to distinguish administrative deviations from criminal conduct based on intent, impact, and accountability. This study contributes to the development of a progressive paradigm in corruption law enforcement and recommends a risk-based legal assessment model to prevent overcriminalization while safeguarding good-faith public officials.
Keywords: Corruption; Justice; Law; Progressive